2010
DOI: 10.1016/j.pain.2010.08.020
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of the Yoga of Awareness program in the management of fibromyalgia

Abstract: A mounting body of literature recommends that treatment for fibromyalgia (FM) encompass medications, exercise and improvement of coping skills. However, there is a significant gap in determining an effective counterpart to pharmacotherapy that incorporates both exercise and coping. The aim of this randomized controlled trial was to evaluate the effects of a comprehensive yoga intervention on FM symptoms and coping. A sample of 53 female FM patients were randomized to the 8-week Yoga of Awareness program (gentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
161
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(175 citation statements)
references
References 57 publications
6
161
2
6
Order By: Relevance
“…In this study, the authors found rates of recruitment (57.14%), adherence (class 87.5%; home practice 93.33%), and retention (75%) were consistent with those reported in other FM and yoga studies investigating feasibility of a yoga intervention for persons diagnosed with FM [63][64][65][66][67][68]. Recruitment rates of 82.8% [64] and 38.6% [65], class adherence rates of 87.5% [64] and 86% [65], and a mean attrition rate of 25.23% ± 10.64% [63][64][65][66][67] were reported in other studies as positive findings for feasibility of the yoga style investigated. Only one of those studies [67] included qualitative data providing participant acceptability data, and none addressed feasibility of the intervention outside of the research setting.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, the authors found rates of recruitment (57.14%), adherence (class 87.5%; home practice 93.33%), and retention (75%) were consistent with those reported in other FM and yoga studies investigating feasibility of a yoga intervention for persons diagnosed with FM [63][64][65][66][67][68]. Recruitment rates of 82.8% [64] and 38.6% [65], class adherence rates of 87.5% [64] and 86% [65], and a mean attrition rate of 25.23% ± 10.64% [63][64][65][66][67] were reported in other studies as positive findings for feasibility of the yoga style investigated. Only one of those studies [67] included qualitative data providing participant acceptability data, and none addressed feasibility of the intervention outside of the research setting.…”
Section: Discussionsupporting
confidence: 87%
“…Costs associated with the purchase of RY equipment available to this study (> $4,000 USD), although high as an initial expenditure, can be amortized over the useful life of the RY equipment, making this initial cash outlay an investment toward future RY intervention classes for other populations, too. However, the requirements for up to six yoga mats with additional extra padding and the instructor to participant ratio of 1:2 is much higher than the normal one to two yoga mats with no additional padding provided in community yoga classes and the one to two yoga instructors for class sizes ranging between 11 to 22 persons reported by other FM/yoga studies [64][65][66]. This higher ratio is consistent with that of the traditional delivery of individualized yoga therapy, suggesting that persons with FM may be better suited to individualized RY therapy sessions as opposed to a group RY delivery design.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[20][21][22] Carson ve ark. [23] fibromiyalji için tedavi seçeneklerinden fibromiyalji (FM) ile başa çıkma becerilerinin geliştirilmesi ve egzersiz yöntemlerinin medikal tedavi ile birlikte uygulanması gerektiğini savunarak, bu amaçla FM ile başa çıkma becerilerini geliştirmek adına farkındalık geliştirme yöntemlerinden olan yoganın etkilerini değerlendir-mişlerdir. Elli üç fibromiyaljili kadın hastaya sekiz hafta boyunca meditasyon, nefes egzersizleri, yoga-odaklı başa çıkma talimatları, grup çalışmaları uygulamış-lardır.…”
Section: Discussionunclassified
“…16 Carson et al conducted a randomised clinical trial and found that Yoga had promising results in the symptoms of FM including pain, fatigue, emotional disturbances and other coping strategies. 17 This study was undertaken to compare the effect of yoga and strengthening exercises on the symptoms of fibromyalgia in women.…”
Section: Introductionmentioning
confidence: 99%